2009
DOI: 10.1080/09500790903082362
|View full text |Cite
|
Sign up to set email alerts
|

Improving scientific argumentation skills by a problem-based learning environment: effects of an elaboration tool and relevance of student characteristics

Abstract: Starting from difficulties that students of education display when they interpret empirical findings and generate scientific arguments, a problem-based e-learning environment was developed. Based on first evaluation data, an elaboration tool was integrated into the learning environment. The tool consisted of a modelling and an explanation part. In order to investigate the effectiveness of this elaboration support, a quasi-experimental field study was carried out in two seminars on scientific methods for advanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 24 publications
3
15
0
2
Order By: Relevance
“…These difficulties are partly due to superficial and mindless learning that leads to knowledge gaps and misconceptions Tyroller, 2005; see also Stark, Puhl, & Krause, 2009). To promote understanding of correlation, the e-learning environment 'Koralle' was developed as a supplement to regular statistics lectures (Tyroller, 2005).…”
mentioning
confidence: 99%
“…These difficulties are partly due to superficial and mindless learning that leads to knowledge gaps and misconceptions Tyroller, 2005; see also Stark, Puhl, & Krause, 2009). To promote understanding of correlation, the e-learning environment 'Koralle' was developed as a supplement to regular statistics lectures (Tyroller, 2005).…”
mentioning
confidence: 99%
“…Similar to the study of Stark et al (2009), the elaboration intervention had a positive impact on mindfulness, meaning that the participants learned with a higher degree of reflection; the scale indicates a deeper involvement with the presented material. The result that only performance on the far transfer task correlated with mindfulness indicates that mindfully learning for this complex task proved especially helpful.…”
Section: Discussionmentioning
confidence: 65%
“…For instance, several studies have shown students' deficits in their ability to interpret statistical data and empirical results in correlation analyses (Krause, 2007;. Here, learning without reflecting the content of what is being learned, often accompanied by motivational deficits, has been identified as an antecedent of knowledge gaps (e.g., Stark, Puhl, & Krause, 2009;Tyroller, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Al diseñar tareas de argumentación, con frecuencia los docentes piden a sus estudiantes elaborar explicaciones esperando que ellos construyan argumentos para responder a la tarea. Si bien la argumentación es el proceso de coordinación e interconexión de planteamientos, evidencia y explicaciones para apoyar o contradecir una postura (Cho & Jonassen, 2002;Evagorou & Avraamidou, 2008;Jeong, 2006;Leitão, 2001Leitão, , 2000moore & marra, 2005;Simon, Erduran & Osborne, 2006;Stark, Puhl & Krause, 2009), las pautas propuestas por los docentes no siempre hacen este tipo de demandas explícitamente, sino que proponen consignas que demandan procesos de descripción o selección de información. Si haciendo descripciones se resuelve efectivamente una tarea que explícitamente requiere argumentación, entonces posiblemente la consigna está enunciando el verbo inapropiado.…”
Section: Discussionunclassified
“…Al menos desde el análisis de contenido, se percibe que los maestros pretendían que sus estudiantes sustentaran sus ideas a partir de los conocimientos disciplinares abordados. Esto resulta llamativo porque los estudios a menudo reportan que los estudiantes con frecuencia argumentan sin aportar o utilizar adecuadamente la evidencia (Scheuer et al, 2010;Stark, Puhl & Krause, 2009). Aunque asegurar lo anterior requeriría observar el desempeño de los estudiantes, por lo menos a partir del análisis realizado es posible afirmar que las tareas explícitamente demandan argumentación utilizando bibliografía académica u obteniendo evidencia o soportes.…”
Section: Discussionunclassified